Factors Associated with Midwife Performance in Integrated Antenatal Care (ANC) Services at the Jambi City Health Center in 2024 - Nurul Qalbi; Asparian Asparian; Hubaybah Hubaybah; Arnild Augina Mekarisce; Usi Lanita (PT. Anagata Sembagi Education, 2025)
Integrated Antenatal Care (ANC) is a health service for pregnant women based on the 10T standard. The main goal is to reduce the maternal mortality rate (MMR), infant mortality rate (IMR) and the probability of mother and child. In its implementation, midwives play an important role so that the performance of midwives greatly affects the quality of Integrated ANC services. In Jambi City, the coverage of Integrated ANC services at the Puskesmas has not yet reached the minimum service standard target of 100% of KI 97.1%, K4 coverage of 94.9% and K6 of 92.3%. The purpose of this study was to determine the factors associated with the performance of midwives in integrated ANC services. This type of research is quantitative with a cros sectional approach. The location of this research was carried out at all Puskesmas in the Jambi City area in November-December 2024. The number of samples was 70 respondents, with the Porpotional random sampling technique. The results showed that there was a significant relationship between motivation with a p value of 0.032 and institutional leadership with the performance of midwives in Integrated ANC services with a p value of 0.016, while experience did not have a significant relationship with the performance of midwives in Integrated ANC services with a p value of 0.088.